Growth evolution of AZO thin films deposited by magnetron sputtering at room temperature - Ramos, R. [UNESP] (2021)
Thin AZO films were grown by RF magnetron sputtering for different deposition times in argon plasmas. Optical, structural, and morphological properties, together with elemental composition, were studied and correlated with the observed effects on the electrical properties and compared with two models of mobility scattering (ionized impurities and grain boundaries). The results suggest that the carrier density in the studied case is limited to below 15% owing to the low ionization efficiency caused by the formation of neutral impurities as homologous phases. While the spread in the mobility during the initial stages of film growth is strongly influenced by grain boundaries, in thicker films the limitation on ion efficiency becomes more significant.